Internal Corporate Governance Practices and Choice of External Auditor in Nigeria: A Logistic Regression Analysis - Kenny Adedapo Soyemi (Bina Nusantara University, 2020)
The research provided empirical evidence on how internal corporate governance practices were proxied by board size, board independence, and share ownership by institutional investors with firm size and leverage as control variables. It might influence the choice of the external auditor, (a dummy proxied with the Big4 versus non-Big4 audit firms dichotomy). The sample was composed of 27 purposely selected quoted non-financial firms spread across 10 sectors on the Nigerian Stock Exchange (NSE). There were 189 firms/year of dataset observations. These secondary panel data were sourced mainly from selected firms’ annual reports and accounts from 2011 to 2017. Moreover, descriptive analysis and test of mean difference were conducted, while the panel logistic regression was adopted as the estimation method. The test of mean difference reveals that many firms with larger board size, board independence, and considerably higher institutional investors engage Big4 auditors. Meanwhile, firms with higher leverage employ non-Big4 auditors. The results from the multivariate analysis show that key determinants of the choice of external auditors are board independence and firm size. This suggests that firms have a higher propensity of choosing a Big4 audit firm as the number of independent board members, as well as their increase in sizes. These findings are mostly consistent with previous studies.